Peranan Penilaian Kinerja Dalam Meningkatkan Kemampuan Karyawan (Studi Kasus PT. Basirih Industrial Banjarmasin) - Wahab HJ, Abd (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
Periodic Performance Assessment can be a clear parameter for employees. Some things that must be considered in the assessment process include: Objectivity assessment is preferred, not on the personality traits or character of a person but on how employees carry out their work. Employees generally argue that performance appraisals will not affect the compensation they earn. This is because based on the consideration that during this salary increase tends to be made equal and mass so there is no difference between outstanding employees and employees not achievers. Management has socialized the Company Rules, Standart Operation Procedure and each employee has known their job description, and this helps to clarify what activities should be done to the employee to achieve the job objectives. Performance appraisal results have not been followed up with guidance or training required by employees. Yet by looking at the results of these assessments it can be seen the strengths and weaknesses of each employee, and can make planning for training to improve the performance. Keyword : Employees Performance